1994
DOI: 10.1111/j.1365-2044.1994.tb03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Infra‐orbital nerve block for relief of postoperative pain following cleft lip surgery in infants

Abstract: Summary The study was conducted on 20 infants scheduled for cleft lip repair surgery. Ten were randomly allocated to receive bilateral infra‐orbital local anaesthetic nerve blocks at the conclusion of surgery with the other 10 receiving bilateral ‘sham’blocks as controls. Postoperative pain relief was assessed using a pain assessment scoring system and by monitoring arterial blood pressure, heart rate and respiratory rate. The mean pain assessment score was significantly higher (i.e. better) (p < 0.05) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 6 publications
0
30
0
2
Order By: Relevance
“…We have not seen any study comparing the effect of infraorbital block performing time to analgesia. Blocks were performed before the operations in all studies, except Ahuja et al's 13 where 1% prilocaine was used postoperatively. To our knowledge, this is the first study evaluating the effect of bupivacaine and infraorbital block performed postoperatively, on postoperative pain relief after cleft lip repair in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…We have not seen any study comparing the effect of infraorbital block performing time to analgesia. Blocks were performed before the operations in all studies, except Ahuja et al's 13 where 1% prilocaine was used postoperatively. To our knowledge, this is the first study evaluating the effect of bupivacaine and infraorbital block performed postoperatively, on postoperative pain relief after cleft lip repair in pediatric patients.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of trigeminal nerve block has been demonstrated in various studies. Ahuja et al [ 17 ] showed a signifi cant improvement in pain score in the infraorbital block group compared to normal saline infi ltration in children scheduled for cleft lip repair. A double-blinded, randomized study also demonstrated a signifi cant reduction in analgesia requirement and pain score in children who had an infraorbital nerve block compared to the conventional peri-incisional infi ltration by the surgeon [ 18 ].…”
Section: Current Literature In Ultrasoundguided Approachesmentioning
confidence: 98%
“…In cases in which the location of the foramen cannot be appreciated, a simple mathematical formula can be utilized [distance from the midline ¼ 21.3 mm þ 0.5 Â age (in years)] [6]. Ahuja et al [7] used infraorbital nerve blocks with local anesthetic compared with normal saline infiltration of the nerve in children scheduled for cleft lip repair and found a significant improvement in pain score in the local anesthetic block group. In 1999 the first double-blind, randomized study [8] published demonstrated the significant improvement in pain scores and decrease in analgesic requirements in children who had an infraorbital nerve block compared with the conventional peri-incisional infiltration by surgeons.…”
Section: Anatomymentioning
confidence: 99%